Analisis Kelayakan Instalasi Listrik Bangunan Sekolah SMA Islam Sultan Agung 1 Semarang : Penelitian - M. Rayhan Fawwazimtiyaz; Sukarno Budi Utomo (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to assess the feasibility of the lighting and electrical system in Building A of SMA Islam Sultan Agung 1 Semarang. Electrical installations play an important role in supporting learning activities, especially since the building has been used for a long time. Therefore, an evaluation is needed to ensure compliance with PUIL 2011 and SNI 03-6197-2000 lighting standards. The method used is a case study with a qualitative approach, using primary data (voltage and current measurements with a clamp meter, and light intensity with a lux meter) and secondary data. The measurement results are compared with the standards to assess the suitability of the distribution system, cable size, and classroom illumination levels. The results show that the electrical system generally complies with PUIL 2011, but there are still shortcomings such as the use of phase cable colors and cable arrangement. In terms of lighting, some classrooms have an intensity below 250 lux, so it is necessary to add or rearrange lights. Regular repairs and maintenance are needed to keep the system safe, efficient, and comfortable to use.